Позбавленці Вінниці за доби НЕПу (1921–1929): статистика та долі людей - Кароєва, Т.; Рога, А. (Краєзнавство, 2024)
У статті з’ясовується специфіка практики визнання позбавленцями у Вінниці за доби НЕПу. Завдання вирішується на основі аналізу списків міських позбавленців 1927 і 1928 рр., біографічних відомостей про окремих осіб. У результаті дослідження підтверджено, що прикордонний статус подільських територій ускладнював проживання політичних ворогів у регіоні, тому серед вінницьких позбавленців не просто переважали, а панували «економічно чужі елементи» (88,1% у 1927 р., 82,3% у 1928 р.), а позбавленців за політичними ознаками було набагато менше, і менше, ніж в УСРР загалом. Атмосфера видавлювання з міста політично ненадійних провокувала на додаткові їх пошуки серед містян, які залишалися. Численні невірні відомості про колишній соціальний та професійний статус людей, хиткі докази їхньої провини та нелояльності до радянської влади приводили до того, що громадяни активно боролися за відновлення своїх виборчих прав, і доволі успішно. Деяким категоріям позбавленців, наприклад, «білогвардійцям» вдавалося перемогти майже у половині оскаржень. Водночас економічні ознаки позбавлення були більш формалізованими та документально засвідченими, тому з ними боротися було набагато складніше. The article delves into the specifics of recognizing people as disenfranchised (the term “lishenets” is commonly used for a person who was deprived of the right to vote; plural “lishentsy”) in Vinnytsia during the period of the NEP. The research task is mainly achieved through analysing the lists of urban disenfranchised people in 1927 and 1928, along with biographical information about specific persons. The research confirms that the border status of the Podillia territories complicated the residence of politically foreign individuals in the region. Therefore, among the disenfranchised people in Vinnytsia, “economically foreign elements” not only prevailed but also dominated (88.1% in 1927, 82.3% in 1928), while disenfranchised people based on political rights were far fewer, and fewer than in total Ukrainian SSR. The atmosphere of expelling politically unreliable individuals from the city led to additional searches for them among the remaining citizens. Numerous inaccurate details about people’s former social and professional statuses, fragile evidence of their guilt, and disloyalty to the Soviet authorities prompted citizens to fight actively to restore their voting rights reasonably successfully. Some categories of disenfranchised people, for instance, the White Guards, managed to win almost half of their appeals. At the same time, the economic indications of disenfranchisement were more formalized and documented, hence more challenging to fight against them.